2018
DOI: 10.1063/1.5050234
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrafast laser generated strain in granular and continuous FePt thin films

Abstract: We employ ultrafast X-ray diffraction to compare the lattice dynamics of laser-excited continuous and granular FePt films on MgO (100) substrates. Contrary to recent results on free-standing granular films, we observe in both cases a pronounced and long-lasting out-of-plane expansion. We attribute this discrepancy to the in-plane expansion, which is suppressed by symmetry in continuous films. Granular films on substrates are less constrained and already show a reduced out-of-plane contraction. Via the Poisson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Similarly, a granular FePt film was prepared at a slightly higher substrate temperature of 650°C by adding approximately 30 volume % of carbon to the sputtering target. X-ray reflectivity measured the sample thicknesses to be about d = 9.5 nm, where the continuous film is covered with an additional 1-nm layer of oxidized Al ( 27 ). According to scanning electron microscopy images of similarly prepared samples (see Supplementary Materials), the size distribution of the FePt nanograins segregated in a carbon matrix within the granular film is centered at approximately 8 nm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a granular FePt film was prepared at a slightly higher substrate temperature of 650°C by adding approximately 30 volume % of carbon to the sputtering target. X-ray reflectivity measured the sample thicknesses to be about d = 9.5 nm, where the continuous film is covered with an additional 1-nm layer of oxidized Al ( 27 ). According to scanning electron microscopy images of similarly prepared samples (see Supplementary Materials), the size distribution of the FePt nanograins segregated in a carbon matrix within the granular film is centered at approximately 8 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The possibility to grow magnetic, oriented nanograins with a high degree of structural order makes this material an ideal candidate for studying the lattice using time-resolved diffraction techniques. In a recent ultrafast x-ray diffraction (UXRD) study, we have found a short-lived lattice contraction along the short out-of-plane c axis of the tetragonal unit cell of a nanogranular FePt film on a substrate, whereas continuous epitaxial thin films merely expanded under otherwise identical excitation conditions (27). Previously, ultrafast electron diffraction experiments had reported a transient c-axis contraction and in-plane expansion for freestanding FePt nanograins (11).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…During the past decade, synchrotron based time-resolved X-ray diffraction (TRXD) has become a versatile probe for characterizing various non-equilibrium phenomena, including the transmission of heat across an interface [14], charge carrier propagation across thin-film interfaces [15] and grain boundaries [16], and the production of anisotropic strain in bulk crystal [17] and multiferroic thin film [18][19][20]. Additionally, laser-based table-top X-ray diffraction methods have enabled probing dynamics at ultrafast time-scales, such as unexpected anisotropic strain development from nanograin film on substrate [21] and a nanoscale transport mechanism in metallic multilayer systems [22]. More recently, X-ray free-electron laser has provided means to resolve ultrafast phase transition phenomena [23,24] that were inaccessible at storage-ring based light sources.…”
Section: Introductionmentioning
confidence: 99%
“…The investigated continuous and granular FePt films are grown in the ordered L1 0 phase onto MgO (100) oriented substrates, which aligns the easy magnetic axis out of plane. A more detailed description of the growth conditions and the structural properties of the samples can be found in Ref [22]. In particular, we mention that the granular film consists of segregated FePt-nanograins embedded in amorphous carbon with a size distribution of FePt particles centered at approximately 10 nm (see Fig.…”
Section: Arxiv:191001413v1 [Cond-matmtrl-sci] 3 Oct 2019mentioning
confidence: 99%